Sustainable Energy Planning and Management with energy scenario modelling, GIS tools and demand projection - Østergaard, Poul Alberg; Duic, Neven (International Journal of Sustainable Energy Planning and Management, 2024)
This 42nd volume of the International Journal of Sustainable Energy Planning and Management includes two articles from the 2023 Sustainable Development of Energy, Water and Environmental Systems (SDEWES) conference series as well as two ordinary articles. The two first articles establish links between the energy systems analysis model EnergyPLAN and respectively the Quintel Energy Transition Model (ETM) and urban building energy modelling to form more comprehensive modelling environments. Third, an article addresses energy systems modelling from a more spatial perspective, with the presentation of the ODHeatMap tool to model the spatial characteristics of heat demand particularly in areas where optimal energy planning data may not be available. Lastly, Vietnam’s economy and energy demand is increasing rapidly, and, in this issue, analyses are presented regarding how ambitions measures in renewable energy utilization and energy efficiency improvements have to beer under different scenarios, for Vietnam to reach its carbon dioxide emission reduction goal.